The Relationship of Cleanliness and Vulva Hygiene in Postpartum Mothers' Perineal Wound Infection - R, Tri Endah; Azizah, Zulfa Nur; Agustina, Melisa (Jurnal Multidisiplin Indonesia, 2024)
Infection during the postpartum period is one of the reasons for the high number of deaths in Mothers. Data from the 2018 WHO shows that infection is the second cause of postpartum maternal deaths in the world. In Indonesia, infection contributes to 10% of deaths of mothers in Indonesia (Sarwono, 2018). Infection perineal wounds were 207 cases (West Java Health Office, 2021). Guard cleanliness and vulva hygiene with Correct can prevent infection of the mother's perineum postpartum. Research objectives This is, for now, the connection between cleanliness and vulva hygiene in infections postpartum mother's perineal wounds at PMB Midwife M in 2023. Types and Designs Study This use method survey analytic observational with a cross-sectional approach. Research sample This is a total sampling technique where the sample size is the same as the population, namely 30 people. Method of collecting data in research: This is done through questionnaires and sheet observations. Then, the data is analyzed in a way univariate and bivariate with the Chi-square test (X 2) at a significant level ? 0.05. The results of the study show that there were six respondents who did not do vulva hygiene well, and 1 of them experienced infection. Got its mark from variable vulva hygiene with incident infection perineal wounds p = 0.000. Results p value <0.05, then Ha is accepted. Yes, there is a connection between cleanliness and vulva hygiene with incident infection perineal wounds in mothers postpartum in PMB M, the expected public can increase the role of active Mothers postpartum to get information about health, especially about vulva hygiene.